Monoklonska protitelesa za preprečevanje migrene - Bratkovič, Tomaž (Farmacevtski vestnik, 2022)
Migraine is a common neurovascular disorder that can severely affect patients’ ability to perform everyday activities, thus posing tremendous disease burden for the affected patients as well as economic burden for the society. Calcitonin gene-related peptide (CGRP), a neuropeptide with vasodilatory and pronociceptive activity, is considered the main neuromodulator involved in migraine pathophysiology. Four therapeutic monoclonal antibodies targeting either CGRP or its cognate receptor constitute a new specific prophylactic antimigraine drug group, displaying favourable efficacy and safety profiles. In addition, due to long biological half-life, monoclonal antibodies require less frequent dosing compared to conventional synthetic antimigraine drugs. here, we review the representative clinical trials and discuss the properties of therapeutic antiCGRP/CGRP-receptor antibodies.
Keywords: CGRP; Klinične raziskave; Migrena; monoklonsko protitelo; Nevropatije; učinkovitost; varnost